Pemahaman dan Kepedulian Pelaku UMKM (Cucian Mobil) Dalam Implementasi Green Accounting Di Kota Pekanbaru - Ade Nila Oktafani; Siti Rodiah; Zul Azmi (Politeknik Raflesia Press, 2025)
This research aims to understand the comprehension and concern of Micro, Small, and Medium Enterprises (MSMEs) involved in car washing regarding the implementation of green accounting at Agatha Carwash in Pekanbaru. This study is designed as descriptive research with a qualitative approach to analyze and describe the comprehension and concern of MSMEs (Car Washes) in the implementation of green accounting in Pekanbaru City. Data collection techniques in this research use observation, interview, and documentation methods. The results of interviews and observations at Agatha Carwash, MK Carwash, and Golden Carwash in Pekanbaru show that they have an understanding and concern for green accounting. This understanding is evidenced by the business owners' knowledge of business costs, their understanding of business costs and the environment, as well as social responsibility to differentiate business costs from personal costs. This level of understanding and concern alone helps maintain the cleanliness of the surrounding environment. Although MSMEs are aware of the importance of maintaining environmental cleanliness, there is still a need to improve their understanding of better green accounting implementation. This is due to limitations in accessing relevant information.